2016
DOI: 10.1007/s10266-016-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of interleukin-33 in gingival crevicular fluids of patients with chronic periodontitis

Abstract: The purpose of this clinical study is to comparatively investigate the interleukin-33 (IL-33) levels in gingival crevicular fluid (GCF), saliva and plasma of patients with periodontal disease as well as periodontally healthy subjects and the association between these levels and clinical parameters. GCF, saliva and plasma samples were collected from systemically healthy, non-smoker chronic periodontitis patients (CP group, n = 20), gingivitis patients (G group, n = 20) and periodontally healthy control groups (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
3
17
1
1
Order By: Relevance
“…The presence of IL‐33 within the oral tissues was recently demonstrated. While periodontal pathogenic bacteria Porphyromonas gingivalis strongly stimulated IL‐33 mRNA expression in gingival epithelial cells, IL‐33 expression is elevated in the inflamed gingival crevicular fluid and gingival epithelium of chronic periodontitis patients . Association of increased IL‐33 level with periodontitis and alveolar bone resorption and loss was also reported .…”
Section: Introductionmentioning
confidence: 93%
“…The presence of IL‐33 within the oral tissues was recently demonstrated. While periodontal pathogenic bacteria Porphyromonas gingivalis strongly stimulated IL‐33 mRNA expression in gingival epithelial cells, IL‐33 expression is elevated in the inflamed gingival crevicular fluid and gingival epithelium of chronic periodontitis patients . Association of increased IL‐33 level with periodontitis and alveolar bone resorption and loss was also reported .…”
Section: Introductionmentioning
confidence: 93%
“…In human, high IL-33 overexpression was recorded in the gingiva of patients affected by CP and may act as a triggering factor for the recruitment of B and T lymphocytes expressing RANK-L [20]. But in gingival crevicular fluid (an inflammatory exudate collected in the periodontal pocket) conflicting results regarding IL-33 levels have been reported in patients affected by CP [2123]. Interestingly, Pg has been described to upregulate IL-33 mRNA expression in gingival epithelial cells through the PAR-2 signaling pathway [24].…”
Section: Introductionmentioning
confidence: 99%
“…[ 21 ] In contrast, a different survey suggested that crevicular fluid was elevated in individuals with gingivitis and chronic periodontitis compared to unaffected individuals, and that IL-33 levels in crevicular fluid were significantly lower in patients with chronic periodontitis than in patients with gingivitis and patients without periodontal disease. [ 23 ] Similarly, in another study, IL-33 activity was found to be associated with RANKL-dependent bone resorption, and thus with chronic periodontal disease. [ 26 ]…”
Section: Discussionmentioning
confidence: 86%